2018
DOI: 10.1016/j.jconrel.2017.11.035
|View full text |Cite
|
Sign up to set email alerts
|

Hollow microneedle-mediated micro-injections of a liposomal HPV E743–63 synthetic long peptide vaccine for efficient induction of cytotoxic and T-helper responses

Abstract: Recent studies have shown that intradermal vaccination has great potential for T cell-mediated cancer immunotherapy. However, classical intradermal immunization with a hypodermic needle and syringe has several drawbacks. Therefore, in the present study a digitally controlled hollow microneedle injection system (DC-hMN-iSystem) with an ultra-low dead volume was developed to perform micro-injections (0.25-10μL) into skin in an automated manner. A synthetic long peptide derived from human papilloma virus formulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(43 citation statements)
references
References 24 publications
0
43
0
Order By: Relevance
“…The NP-peptide/4M2e-layered nanoparticle group showed much higher levels of NP 147 -and NP 55 -specific IFN-γ-secreting splenocytes. In previous studies, peptide mixture reactivation of splenocytes indicated the successful induction of vaccine-specific cellular immune responses (34,35). We measured levels of IFN-γ, IL-4, and IL-2 from the splenocyte culture medium in the presence of a peptide pool containing equal amounts of 4M2e and the NP peptide 3 wk after the boosting immunization.…”
Section: Np-peptide/4m2e-layered Nanoparticles Induced Robust Protectivementioning
confidence: 99%
“…The NP-peptide/4M2e-layered nanoparticle group showed much higher levels of NP 147 -and NP 55 -specific IFN-γ-secreting splenocytes. In previous studies, peptide mixture reactivation of splenocytes indicated the successful induction of vaccine-specific cellular immune responses (34,35). We measured levels of IFN-γ, IL-4, and IL-2 from the splenocyte culture medium in the presence of a peptide pool containing equal amounts of 4M2e and the NP peptide 3 wk after the boosting immunization.…”
Section: Np-peptide/4m2e-layered Nanoparticles Induced Robust Protectivementioning
confidence: 99%
“…To induce strong functional cytotoxic and potent T-cell responses, van der Maaden et al. 75 developed hollow microneedle injection system combined with the synthetic long peptide as a therapeutic cancer vaccine. As compared to intradermal injections, the promising strategy enables much lower volumes, further leading to improve immunogenicity and effectiveness of tumor vaccine formulations.…”
Section: Applications Of Microneedlesmentioning
confidence: 99%
“…Drug dispersion can be filled into the hollow MNs and deposited into the epidermis following MN insertion. An extra pump can be utilized to change the speed of drug solution carefully and refill the drug without removing the MNs, which makes continuous delivery of the drug possible [99]. Hollow MNs are also widely used to collect ISF [34] and blood [18].…”
Section: Hollow Mnsmentioning
confidence: 99%